Hubungan Dukungan Sosial Dengan Burnout Akademik Pada Siswa Sekolah Menengah Atas - Dewi, Bunga Nur Indah; Nuryani, Reni; Lindasari, Sri Wulan (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
The adolescent stage in secondary education in Indonesia is a crucial stage in adolescent development, with curricula more complex than the elementary education stage. High academic challenges and developmental demands can lead to physical and emotional burnout in students. Academic burnout is caused by the length of school hours, too much activity, and too much work. Another factor causing academic burnout is a lack of social support. Social support plays an important role in creating a comfortable, motivated learning environment, providing support and assistance that can ultimately help reduce burnout. The study aims to find out the relationship between social support and academic burnout in high school students. The research method used is quantitative correlational research. Research samples of students of classes X and XI with a total of 258 students were taken using stratified random sampling. The instruments used include social support questionnaires that are structured based on House's aspects to measure the level of social support and a Maslach Burnout Inventory-Student Survey (MBI-SS) questionnary to measures the burnout rate. Data analysis is done univariately and bivariately using a chi-square test. The results show that there is a significant link between social support and academic burnout in students, which shows that social support plays a role in reducing academic Burnout and improving academic performance.